Reproductive health awareness among female university students at Saudi Arabia - Alomani, Alanood; Alfaifi, Amjad; Almutairi, Asma; Alahmed, Reem; Alkhalid, Nora; Mortada, Eman M. (International Journal Of Community Medicine And Public Health, 2023)
Background: Reproductive health is a major part of a woman’s life to ensure a healthy life for both mothers and their babies. However, most women do not have the proper knowledge and awareness of that subject. Objectives were to assess the awareness of reproductive health among Saudi female university students and to determine the factors associated with the level of awareness. Methods: A cross-sectional study conducted among 347 participants, using multi-stage stratified sampling. A structured self-administered questionnaire was used to assess the knowledge level of the five-major component of reproductive health. Results: The results revealed an average level of knowledge about reproductive health (49.4%) among the college students. There was a significant association between having children, mother’s working status, and father educational level, family income and participant reproductive health knowledge (p=0.02, 0.005 and 0.02) respectively. Although 77.1% of the participants had good knowledge of menstrual health and hygiene, they showed misconceptions. The knowledge about family planning, prenatal and antenatal were high 66.6% and 53.9%. The level of knowledge on sexually transmitted diseases was 58% high among students and only 40% have heard of HIV/AIDS but other diseases were less recognized. Conclusions: The knowledge of reproductive health is considered poor. Father’s education level and family income were associated with the level of a student’s knowledge. Educational session about RH is needed among students with focus on menstrual health and hygiene, antenatal care, family planning, breastfeeding, and sexually transmitted diseases.